The Impact of Local Wisdom-Based Tourism on MSME Income Growth: The Mediating Role of Digital Marketing - Sumarni, Sumarni; Prabowo , Rahmat Eko; Hadijah, Andi St. (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Tourism based on local wisdom has great potential in encouraging regional economic growth, especially for MSMEs. However, there are still many MSMEs that face obstacles in increasing revenue due to limited market access, ineffective marketing strategies, and low adoption of digitalization. This study aims to analyze the influence of tourism based on local wisdom on MSME income by mediating marketing digitalization. Using quantitative methods with explanatory research design. Data was collected through questionnaires distributed to MSMEs in the Kajang Bulukumba tourist area. The analysis technique used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study show that tourism based on local wisdom has a positive and insignificant effect on the income of MSMEs. Tourism variables based on local wisdom have a significant negative effect on marketing digitalization, as well as marketing digitalization has a significant negative effect on MSME income. This shows that the role of digitalization as a mediator is not optimal. These findings imply the need for local governments and stakeholders to strengthen the digital capacity of MSMEs through training, mentoring, and facilitation so that the potential of tourism based on local wisdom can be maximized in increasing MSME income.